Critical Genes in White Adipose Tissue Based on Gene Expression Profile Following Exercise - Wang, Haitang; Lee, J.- H.; Tian, Ye (International Journal of Sports Medicine, 2019)
Exercise is recognized as an effective method to prevent obesity and alleviate metabolic diseases. Browning of white adipose has the advantage of decreasing insulin resistance. We aim to identify critical differentially expressed genes (DEGs) in white adipose tissue after exercise. We downloaded the gene dataset GSE68161 of C57BL/6 mice from the Gene Expression Omnibus (GEO) database. Then, we analyzed the effect of exercise on up-regulated and down-regulated DEGs by GEO2R and performed protein-protein interaction network analyses. We then identified hub-genes in white adipose tissue and crosstalk genes of a single pathway by the STRING database and Cytoscape. In this study, 72 DEGs were screened out, and they mainly function in glycerol-3-phosphate dehydrogenase activity and in the primary biological process of fatty acid oxidation regulation. The top 5 hub-genes screened out were SLC27A1, COX7A1, PPARGC1A, FABP3, and UCP1. The 3 crosstalk genes found were SLC27A1, SLC27A2, and PPARA. These 3 genes might function as a bridge of the PPAR signaling pathway, adipocytokine signaling pathway and the insulin resistance pathway. SLC27A1 is critical gene for the interactions of signaling pathways in subcutaneous white adipose tissue. Therefore, further relationships between the browning of white adipose and insulin resistance need to be studied.
Keywords: exercise; differentially expressed gene; enrichment analysis; network